Prose, Verse and Authorship in Dream of the Red Chamber: A Stylometric Analysis. Issue 4 (2nd October 2021) - Zhu, Haoran; Lei, Lei; Craig, Hugh
ABSTRACT: In this study, we provide a quantitative analysis of prose and verse in the classical Chinese novel, Dream of the Red Chamber (DRC), and discuss the implications for the disputed authorship of the novel. Firstly, we examine the amount of verse in across the chapters of DRC, and compare the style of the verse and prose portions of DRC . Secondly, a Principal Component Analysis (PCA) of DRC is performed based on the prose portions of the novel. Lastly, we discuss the implications of our experimental results for authorship attribution as well as descriptive stylistic analysis of DRC . Our authorial analysis largely confirms the findings of some previous studies that the novel has two authors. Meanwhile, stylistic analyses of the prose portions of the novel yield new and interesting results, which demonstrates that stylometric tools can be used to facilitate descriptive studies of classical Chinese literature.